The nature of tree growth and the "age-related decline in forest productivity" - Weiner, Jacob; Thomas, Sean C. (Oikos, 2001)
The decline in the productivity of forests after a period of growth has been much discussed in recent years, with numerous research papers and several review articles on the topic. Most of these articles have focussed on alternative physiological mechanisms to explain this phenomenon. Proposed mechanisms include (a) an altered balance between photosynthetic and respiring tissues, (b) decreasing soil nutrient availability, (c) reduced photosynthetic rates due to increasing limitations to water transport, and (d) changes in allocation. At the recent meeting of the Ecological Society of America (5-10 Aug. 2000, Snowbird, Utah), there was a well-attended discussion entitled "What DOES [emphasis theirs] cause age-related decline in forest productivity?" Behind many of the discussions lies the hope that if we can understand what causes the decline in productivity with stand age, perhaps we can do something about it. We contend that much of this discussion has taken place at the wrong scale, that proximate and ultimate causes have been confused, and that an essential perspective has been ignored. This perspective is simply that trees, like all organisms, exhibit sigmoid growth curves, and that age- and/or size-dependence of growth rates is an expression of this pattern. In this note we present three fundamental and related points which we believe have not been appropriately considered in the discussions to date.